Three years follow up in patients with stage III breast cancer: Single institution experience - Stojkovski, Igor; Kraleva, S.; Smichkoska, Snezhana; Crvenkova, Simonida (American Society of Clinical Oncology (ASCO), 2006)
10752 Background: Purpose of this study is to estimate impact of different prognostic factors and treatment procedures on overall survival of patients with stage III breast cancer, treated at the Institute of Radiotherapy and Oncology (IRO) in Skopje, Macedonia. Methods: Retrospective analysis of patient records of forty four patients with stage III breast was performed. Before admitting at IRO, each patient undergoes surgical treatment, which comprises of radical mastectomy with ipsilateral axillary dissection. Patients were classified according to TNM system of AJCC. All patients were divided in groups according to primary tumor size (unknown, less than 5 cm and more than 5 cm), positive lymph nodes (4–9 positive lymph nodes or more than 9 positive lymph nodes), adjuvant chemotherapy (CMF like, antracyclines based and taxanes based) and elective radiation of thoracic wall and regional lymph nodes (with or without radiation). Results: Statistical analysis of data was performed with Kaplan Meier estimation and log-rank test. In our series only tumor size has significant impact on overall survival of patient (p = 0.0134). Nodal status, type of adjuvant chemotherapy used and radiation has no significant impact on overall survival. Conclusions: Further analysis and longer follow up of this subgroup of patients is necessary to estimate value of different prognostic factors and treatment modalities. No significant financial relationships to disclose.